1983
DOI: 10.1901/jeab.1983.39-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Discriminative Control by Social Behavioral Stimuli

Abstract: Visual discriminative control of the behavior of one rat by the behavior of another was studied in a two-compartment chamber. Each rat's compartment had a food cup and two response keys arranged vertically next to the clear partition that separated the two rats. Illumination of the leader's key lights signaled a "search" period when a response by the leader on the unsignaled and randomly selected correct key for that trial illuminated the follower's keys. Then, a response by the follower on the corresponding k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Łopuch and Popik () studied coordination between pairs of rats and found that coordination decreased under conditions in which opaque barriers were used to block visual stimulation. However, when Tan and Hackenberg () studied rats under similar conditions, with opaque and clear barriers, they did not replicate their results (also see Hake, Donaldson, & Hyten, ). Tan and Hackenberg argued that the different findings may be attributable to the rats' experience with the coordination task.…”
Section: Discussionmentioning
confidence: 94%
“…Łopuch and Popik () studied coordination between pairs of rats and found that coordination decreased under conditions in which opaque barriers were used to block visual stimulation. However, when Tan and Hackenberg () studied rats under similar conditions, with opaque and clear barriers, they did not replicate their results (also see Hake, Donaldson, & Hyten, ). Tan and Hackenberg argued that the different findings may be attributable to the rats' experience with the coordination task.…”
Section: Discussionmentioning
confidence: 94%
“…Early studies using pair-housed animals reported social facilitation of lever pressing maintained by food (Strobel, 1972) and water (Henning and Zentall 1981) reinforcement. In a similar line of research, social learning was used to explain the facilitation of responding in a “follow-the-leader” task in which food delivery was contingent on successfully imitating the behavior of a companion behind a transparent partition (Hake et al 1983). Social facilitation has also been observed in cats using a shock-avoidance procedure (John et al 1968) and rats using a candle-flame avoidance procedure (Bunch and Zentall 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the role of social-learning theories in substance use is limited – ethical constraints limit the degree to which substance use can be modeled and/or reinforced in human populations, and very few preclinical models permit animals to model and/or reinforce the substance use behavior of peers. However, human laboratory studies report that individuals will often imitate the drinking behavior of a model consuming alcohol (Caudill and Marlatt, 1975; Lied and Marlatt, 1979; Larsen et al, 2009), and animal studies report that responding maintained by nondrug reinforcers (e.g., food, water, escape from shock) is facilitated if a subject is allowed to observe an experienced model (John et al, 1968; Strobel, 1972; Bunch and Zentall, 1980; Henning and Zentall, 1981; Hake et al, 1983). To date, very few studies have extended these findings to responding maintained by intravenous drug administration, the most common method by which drug reinforcement is examined in the laboratory.…”
mentioning
confidence: 99%